Pengaruh Intervensi Edukasi terhadap Tingkat Pengetahuan dan Sikap Ibu Mengenai Penatalaksanaan Diare pada Balita. - Titin Supriatin; Nyimas Heny Purwati; Lindesi Yanti; Maya Sari; Yani Nurhayani (Pusat Riset dan Inovasi Nasional, 2025)
Diarrhea remains a major cause of morbidity and mortality in children. It is crucial for mothers to have the right knowledge and attitudes in prevention efforts. One step that can be taken is to provide easy and relevant health education regarding early diarrhea prevention. The study aims to determine the effect of health education on the level of knowledge and attitudes of mothers about diarrhea in toddlers. The study used a quasi-experimental approach with a one-group pretest-posttest, with purposive sampling and a sample size of 34 people. The analysis test of this study was the dependent T-test for the level of maternal knowledge, and the Wilcoxon Signed-Rank Test for attitudes. Based on the analysis results, there was a difference in the average knowledge score between before and after the educational intervention. The average pre-test knowledge score was 4.76 (SD = 1.50) and increased to 8.41 (SD = 2.36) post-test. For the attitude variable, the average pre-test score was 7.71 (SD = 2.05) and the post-test score increased to 16.00 (SD = 0.82). The education was proven to be effective in improving mothers' knowledge and attitudes. Health workers continuously provide education to improve knowledge and attitudes.